Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Divisi Fashion & Forwear PT Mitra Adi Perkasa Tbk Area Bandung - Setyawan, Bagus; Zulganev, Zulganev (Universitas Sang Bumi Ruwa Jurai, 2024)
This research aims to analyze the influence of work motivation and work environment on employee performance. The research was conducted in the Fashion Footwear Division of Pt Mitra Adi Perkasa Tbk Bandung Area. The research method used was a quantitative method with a sample size of 58 people taken from the entire population. The sampling technique used is a saturated sample or census. The data analysis technique used is multiple linear regression analysis using SPSS Series 26.0 New Version statistical software. This research was carried out by distributing questionnaires, interviews and observation as data collection techniques. The research results show that work motivation and work environment have a positive effect on employee performance in the Fashion and Footwear Division of PT Mitra Adi Perkasa simultaneously. The results of the analysis show that the influence of work motivation and work culture on employee performance is 27.7% and the remaining 72.3% is influenced by other variables not examined in this research.